The Neoliberal Convergence of European Industrial Relations: Economic Inevitability or Result of European Political Choices?. Issue 40 (September 2019) - Jefferys, Steve
Abstract : The central argument of Lucio Baccaro and Chris Howell's analysis of European industrial relations over the past four decades (with a statistical analysis of fifteen countries and detailed chapters on five) is that 'employer discretion' has increased everywhere, although this is evidenced more in some countries than in others. There can be little disagreement on this, nor with their using this general trend in their argument against the (now less strident) 'varieties of capitalism' denials of 'convergence' in employment relations. But the authors neglect the way capital manifests itself through the choices made by living capitalists and their managers. Nevertheless, they make an important contribution to understanding how far Western Europe's capitalist classes and managers have, from the 1980s to the 2000s, acted in new political and industrial ways as a result of having embraced, or been taken over by, a 'mass movement' of managerialism in the US and Western Europe closely allied to the new free-market political right, and the much higher levels of interpenetration of US and Western European capital.